Conformational Studies on Divalent Five-Membered Ring C4H4M (M = C, Si, Ge, Sn and Pb) - Vessally, E.; Azimi, A.; Nikoorazm, M.; Goudarzi Afshar, H. (Asian Journal of Chemistry, 2010)
Sum of electronic and thermal energy differences between singlet and triplet states, ΔEt-s; enthalpy differences, ΔHt-s; free energy differences, ΔGt-s, are calculated for C5H4, C4H4Si, C4H4Ge, C4H4Sn and C4H4Pb at B3LYP/6-311++G (3df,2p) level of theory. Triplet state of carbene, C5H4, appears planar and ground state while its corresponding singlet state is nonplanar. In contrast, its analogues, C4H4M (M = Si, Ge, Sn and Pb) in both singlet and triplet states have planar structures with the ground state singlet. The order of energy differences between singlet and triplet, ΔGt-s, is: plumbylenes > stanylenes > germylenes > silylenes > carbene.